Factors Associated with the Incident of Leukorrhea in Adolescent Girls - Anik Sulistiyanti; Ana Yuliana; Alda Ayu Jifaniata (GLOBAL HEALTH SCIENCE GROUP, 2022)
Leukorrhea in adolescents is a problem that often occurs and interferes with reproductive health system. According to Sirait, 2021 states that vaginal discharge is a physiological thing for a woman, almost 75% of women experience vaginal discharge in conditions of ovulation, before menstruation or after menstruation. But most women do not know about vaginal discharge and its causes so that if not treated properly it will cause infertility and is an early symptom of uterine cancer and various problems such as sexually transmitted infections. The purpose of this study was to determine the factors associated with the incidence of leukorrhea in adolescent girls in the Ngasinan village, Sukoharjo. The research uses an Analytical Survey with a research design that is a Cross Sectional approach. The population is all young women in the Ngasinan Sukoharjo Village area with a sample technique using Simple Random Sampling, totaling 120 respondents. Data analysis used Univariate analysis and Chi-Square test. Based on the bivariate analysis using the Chi-Square test, the age variable was obtained ρ Value = 0,004< 0,05, knowledge ρ Value = 0,001< 0,05, attitude ρ Value = 0,003 < 0,05, using pantyliner ρ Value = 0,001 < 0,05, and using of vaginal cleaning fluid ρ Value = 0,004 < 0,05. This study has a significant relationship between age, knowledge, adolescents, attitudes, use of pantyliners and use of vaginal cleaning fluids with the incidence of leukorrhea in adolescent girls.